THE IMPACT OF OWNER PERCEPTIONS ON CORPORATE GOVERNANCE TOWARDS TAX COMPLIANCE OF SMES - Agusti, Rosalita Rachma (FIA UB, 2020)
This research studies tax compliance behavior of SMEs business owners by observing perceptions of corporate governance principles that are appropriate for SMEs. The owner's perception of the importance of implementing the principles of corporate governance SMEs in the business is believed to provide a strong foundation for the business continuity of the SMEs. The study was conducted by conducting a survey of SMEs business owners in Malang City as a city that serves as a barometer of creative economic development. The survey was conducted by distributing questionnaires that use a Likert scale to measure perceptions of business actors. The results showed that SMEs owners' perceptions of the importance of implementing corporate governance principles including information and communication, external audit, internal control and stakeholders influence the perception of business actors on tax compliance